Targeting Programmed Cell Death Using Small‐Molecule Compounds to Improve Potential Cancer Therapy. Issue 6 (30th June 2016) - Ke, Bowen; Tian, Mao; Li, Jingjing; Liu, Bo; He, Gu
Abstract: Evasion of cell death is one of the hallmarks of cancer cells, beginning with long‐established apoptosis and extending to other new forms of cell death. An elaboration of cell death pathways thus will contribute to a better understanding of cancer pathogenesis and therapeutics. With the recent substantial biochemical and genetic explorations of cell death subroutines, their classification has switched from primarily morphological to more molecular definitions. According to their measurable biochemical features and intricate mechanisms, cell death subroutines can be divided into apoptosis, autophagic cell death, mitotic catastrophe, necroptosis, parthanatos, ferroptosis, pyroptosis, pyronecrosis, anoikis, cornification, entosis, and NETosis. Supportive evidence has gradually revealed the prime molecular mechanisms of each subroutine and thus providing series of possible targets in cancer therapy, while the intricate relationships between different cell death subroutines still remain to be clarified. Over the past decades, cancer drug discovery has significantly benefited from the use of small‐molecule compounds to target classical modalities of cell death such as apoptosis, while newly identified cell death subroutines has also emerging their potential for cancer drug discovery in recent years. In this review, we comprehensively focus on summarizing 12 cell death subroutines and discussing their corresponding small‐molecule compounds in potential cancer therapy. Together, these inspiring findings may provide more evidence to fill in the gaps between cell death subroutines and small‐molecule compounds to better develop novel cancer therapeutic strategies.